Características bioeconômicas de cordeiros Santa Inês e mestiços Dorper×Santa Inês no modelo precoce de produção - Souza, Daniel de Araújo (2015)
The experiment was conducted to evaluate the bioeconomic performance and the carcass and meat traits of Santa Inês and Dorper×Santa Inês lambs under the early biological model as to evaluate the correlations between traits obtained in vivo, in the carcass and in the meat. A total of twenty-four lambs were used in this trial under a fully randomized design. The lambs were housed and creep fed until weaning at 62 days of age. After weaning, they were sent to a feedlot for finishing with a high energetic diet until slaughter, which occurred when they reached 3 mm of subcutaneous fat thickness. From data of performance of 24 lambs was projected a feedlot for finishing of weaned lambs with static capacity for 100 animals by finishing cycle. The Dorper crossbreed lambs exhibited a higher daily gain (223.8 g/day) than the Santa Inês pure lambs (168.1 g/day) and also were faster in reaching the slaughter fat thickness (132 days). Significant differences were observed between the crosses and Santa Inês lambs for the carcass weight, rib eye area, carcass and leg compactness indexes, weight and dressing of commercial cuts and muscle:bone ration. The chest width and body compactness index obtained in vivo and muscle depth and rib eye area obtained by real time ultrasound present significant (P<0.001) and positive (0.72 ≤ r ≤ 0.94) association with primary carcass traits as rib eye area, conformation and carcass compactness index. There was moderate correlation (P<0.01) between body condition score and the fatness (r=0.54) of carcass and the intramuscular fat (r=0.56) of meat. The economic analysis showed positive results, profitability of 22.1% and the lower costs for the ¾ Dorper×Santa Inês feedlot. The compounds with highest influence on production costs of the feedlot were the purchase of weaned lambs and the feeding. According to the results obtained and under the described experimental conditions, it may be concluded that at the same maturity level, the growth performance, the age at slaughter and the main carcass characteristics were improved by crossbreeding of Santa Inês ewes with Dorper rams, making possible the use of local sheep breeds to meet efficiently the needs of domestic market. The real time ultrasound proved to be an efficient method to estimate the muscularity (r=0.78), rib eye area (r=0.72) and subcutaneous fat thickness (r=0.56) of the lambs. The finishing at feedlot is economically viable with lambs of greater biological potential for weight gain and for use of feeds, being the growth rate, feed conversion and finishing precocity the variables that have significant impact on the economic and productive efficiency of feedlot.